2022
DOI: 10.3390/ijms23116159
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Alleviates Visceral Pain and Depression via Inhibition of P2X7 Receptor

Abstract: Chronic visceral pain can occur in many disorders, the most common of which is irritable bowel syndrome (IBS). Moreover, depression is a frequent comorbidity of chronic visceral pain. The P2X7 receptor is crucial in inflammatory processes and is closely connected to developing pain and depression. Gallic acid, a phenolic acid that can be extracted from traditional Chinese medicine, has been demonstrated to be anti-inflammatory and anti-depressive. In this study, we investigated whether gallic acid could allevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…11 GA could modulate depressive behaviors and affect BBB permeability, which is related to its anti-inflammatory effect. 28,29 TPS have shown antioxidant and immune regulation effects which reduce inflammatory cytokines through an anti-inflammatory effect to inhibit the development of depression. 30 Caffeine is the most abundant alkaloid which could be absorbed through the intestinal tract and cross the BBB to modulate neurotransmitters to improve mood.…”
Section: Papermentioning
confidence: 99%
“…11 GA could modulate depressive behaviors and affect BBB permeability, which is related to its anti-inflammatory effect. 28,29 TPS have shown antioxidant and immune regulation effects which reduce inflammatory cytokines through an anti-inflammatory effect to inhibit the development of depression. 30 Caffeine is the most abundant alkaloid which could be absorbed through the intestinal tract and cross the BBB to modulate neurotransmitters to improve mood.…”
Section: Papermentioning
confidence: 99%
“…Essential oil from Liquidambar formosana leaves has certain anti-in ammatory activity, which can ameliorates in ammatory response in lipopolysaccharideactivated mouse macrophages [31] .The remarkable clinical e cacy of CYN tablets may come from the comprehensive effect of multi-components and multi-targets of different herbs. Identi cation and analysis using liquid chromatography-tandem mass spectrometry (LC-MS) revealed that the main active components of CYN (a TCM formula) include quercetin, gallic acid, catechol, luteolin, kaempferol, etc., which possess various biological activities such as anti-in ammatory, visceral pain relief, antioxidant, alleviation of visceral hypersensitivity, and modulation of gut microbiota [32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…The open field test (OF) imitates unsafe surroundings, evaluates animals’ autonomous behavior, and reveals how tense the animals are ( Cheng et al, 2022 ; Hou et al, 2022 ; Wang L. P. et al, 2022 ; Wen et al, 2022 ). A 30 min dark adaptation was conducted before initiating the test.…”
Section: Methodsmentioning
confidence: 99%